INTER REGIONAL GOVERNMENT COOPERATION:ADMINISTRATIVE LAW PERSPECTIVE - Sujatmoko, Emanuel; Wahyuni, Indria; Abrianto, Bagus Oktavian (UI Scholars Hub, 2016)
As it stated in the considering provision of Law number 32 year 2004 on Local government that “regional administration aimed to accelerate the realization of public welfare through improvement, services, empowerment, and community involvement, as well as enhancing regional competitiveness with underlined to the principles of democracy, equality, justice, privilege and specificity of a region within the system of the Republic of Indonesia”. To realize these goals, cooperation between local governments is needed, it is given that many regional affairs cannot be done by themselves unless in cooperation with other local governments. According to existing legal regulation, the inter-regional government cooperation is stated in various legal forms. Article 195 of Law Number 32 year 2004 choose Joint Decree as the legal form of inter-regional cooperation, while article 5 of the Government Regulation Number 50 year 2007 regarding Local Cooperation establish the cooperation in the form of Agreement. Besides those two legal form of inter-regional cooperation, Ministerial Regulation No. 22 of 2009 on the Technical procedure on inter-regional cooperation stipulate “memorandum of understanding” as form of understanding between two parties before the agreement is signed. Memorandum of understanding and agreement as the legal form of the inter-regional government cooperation is not recognized as legislation product of local government as it promulgated in Article 3 of Ministerial Regulation No. 53 of 2011 on the Establishment of the Regional Legislation Products. This paper aimed to identify the legal form of inter regional cooperation, such legal form is an important to bring legality principle for government action in creating cooperation.